The digital transformation of regulated companies in an era of adversity: Empirical study of the impact of digital maturity on organizational resilience from a financial performance perspective – The case of financial companies in Morocco - ESSEMAN , Hamza; NAFZAOUI , Mohamed Achraf (Revue Internationale des Sciences de Gestion, 2025)
An uncertain and complex economic and financial environment is forcing companies to act quickly and constantly to reinvent their strategies. In this context, digital transformation has become an essential and inevitable step in adapting to market changes and remaining competitive, while resilience has emerged as a key asset enabling companies to successfully respond to external pressures. This study examines the link between digital maturity and organizational resilience, as well as their influence on the financial performance of companies in the Moroccan financial sector, which face constant disruption. The results of this study highlight that digital maturity and organizational resilience are essential dynamic capabilities, particularly in a context marked by environmental turbulence, and as such actively contribute to improving financial performance.